Health care provider's perceived factors for the increased practice of caesarean delivery in North West Amhara referral hospitals, Ethiopia, 2022: a qualitative study - Ayele, Mulat; Berta, Marta; Zewudie, Amare; Shitie Lake, Eyob; Yilak, Gizachew; Tilahun, Befkad Derese; Aklil, Mastewal Belayneh (Frontiers in Global Women's Health, 2025)
BackgroundCaesarean delivery is an essential obstetric intervention to reduce maternal and newborn mortality in emergencies. However, in Ethiopia, there is a high prevalence of caesarean deliveries. Therefore, this study aimed to explore the factors perceived by healthcare providers that contribute to the excessive rates of caesarean deliveries in North West Amhara referral hospitals, Ethiopia, in 2022.MethodsA phenomenological study design was employed, utilizing semi-structured interview guide for data collection. Fifteen healthcare providers working in referral hospitals in the north-western region of Amhara were interviewed using a heterogeneous purposive sampling approach until data was saturated. Transcribed interviews were translated coded and finally thematic analyses were employed using Open Code 4.0 software.ResultsHealthcare providers observed a significant increase in the frequency of caesarean deliveries. Multiple factors were identified as contributing to this rise, including the involvement of medical students, the use of cardiotocography, a decline in instrumental deliveries, inadequate trial of labor after previous caesarean deliveries, and the absence of clear indications for performing caesarean deliveries for social or maternal requests. Notably, patients who had received care in private clinics were more likely to undergo caesarean deliveries.ConclusionCaesarean deliveries were observed to be performed based on subjective or approximate indications, rather than clear obstetric indications. Encouraging greater emphasis on trial of labor, instrumental delivery, and performing caesarean deliveries only when there are definitive obstetric indications, rather than for social or maternal requests, can contribute to reducing the prevalence of caesarean delivery rates.